How does who-you-sell-to affect your extent of market participation? evidence from smallholder maize farmers in Northern Ghana - Agness Mzyece; Aleksan Shanoyan; Vincent Amanor-Boadu; Yacob Abrehe Zereyesus; Kara Ross; John N. Ng'ombe (Cogent Economics & Finance, 2023)
This study examines the effect of marketing channel choice on the extent of market participation, with the goal of helping farm managers and policymakers to identify ways of enhancing market participation outcomes. The study uses data from 383 smallholder maize farmers who were part of the respondents to the Agriculture Production Survey conducted in 2014 and the Population-Based Survey conducted in 2012 in Northern Ghana. Econometric analysis was performed using the double hurdle model to account for data censoring in a more flexible way. Findings indicate that smallholder farmers in Ghana sell larger maize quantities when they sell to aggregators than when they sell directly to consumers. By changing from selling to consumers to selling to aggregators, farmers can increase the amount of maize sold by 128.46 kg conditional on participation and by 43.41 kg unconditional on participation. This is potentially due to the scale advantages and non-pecuniary cost savings that aggregators present. The results imply that facilitating access to aggregator-type middlemen may improve market participation in markets where market infrastructure and institutions are not developed enough to substantially lower pecuniary and non-pecuniary marketing costs of selling directly to consumers.
Keywords: 330; double hurdle model; market participation; marketing channel; marketing costs; Northern Ghana